Exploration of the Possible Relationships Between Gut and Hypothalamic Inflammation and Allopregnanolone: Preclinical Findings in a Post-Finasteride Rat Model - Silvia Diviccaro; Roberto Oleari; Federica Amoruso; Fabrizio Fontana; Lucia Cioffi; Gabriela Chrostek; Vera Abenante; Jacopo Troisi; Anna Cariboni; Silvia Giatti; Roberto Cosimo Melcangi (Biomolecules)
Background: Finasteride, a 5α-reductase inhibitor commonly prescribed for androgenetic alopecia, has been linked to persistent adverse effects after discontinuation, known as post-finasteride syndrome (PFS). Symptoms include neurological, psychiatric, sexual, and gastrointestinal disturbances. Emerging evidence suggests that PFS may involve disruption of sex steroid homeostasis, neuroactive steroid deficiency (notably allopregnanolone, ALLO), and gut–brain axis alterations. Objective: This study aimed to investigate the effects of finasteride withdrawal (FW) in a rat model and evaluate the potential protective effects of ALLO on gut and hypothalamic inflammation. Methods: Adult male Sprague Dawley rats were treated with finasteride for 20 days, followed by one month of drug withdrawal. A subgroup received ALLO treatment during the withdrawal. Histological, molecular, and biochemical analyses were performed on the colon and hypothalamus. Gut microbiota-derived metabolites and markers of neuroinflammation and blood–brain barrier (BBB) integrity were also assessed. Results: At FW, rats exhibited significant colonic inflammation, including a 4.3-fold increase in Mφ1 levels (p < 0.001), a 2.31-fold decrease in butyrate concentration (p < 0.01), and elevated hypothalamic GFAP and Iba-1 protein expression (+360%, p < 0.01 and +100%, p < 0.01, respectively). ALLO treatment rescued these parameters in both the colon and hypothalamus but only partially restored mucosal and BBB structural integrity, as well as the NF-κB/PPARγ pathway. Conclusions: This preclinical study shows that FW causes inflammation in both the gut and hypothalamus in rats. ALLO treatment helped reduce several of these effects. These results suggest ALLO could have a protective role and have potential as a treatment for PFS patients.